2014
DOI: 10.5430/jha.v3n3p107
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of person-centred care: management perspective

Abstract: Objective: In this study the implementation of a care model was examined in a public hospital in Sweden. The aim was to identify, from the management perspective, barriers and facilitators with respect to the implementation. A further aim was to study the explanatory power of a theoretical framework, normalization process theory (NPT). Method: Semi-structured interviews were conducted with all of the members of a hospital departments’ managerial group. Interview transcripts were analysed by means of directed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…With some restrictions suggested by May et al, NPT could be used to predict the outcome of implementation processes [25] . Alharbi et al mean that NPT has a weakness in the sense that the theory does not take into account the time dimension of implementation processes [38] , a notion that is also supported by the present results. Participants on some of the studied wards suggested that more time is required in relation to the implementation process.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…With some restrictions suggested by May et al, NPT could be used to predict the outcome of implementation processes [25] . Alharbi et al mean that NPT has a weakness in the sense that the theory does not take into account the time dimension of implementation processes [38] , a notion that is also supported by the present results. Participants on some of the studied wards suggested that more time is required in relation to the implementation process.…”
Section: Discussionsupporting
confidence: 85%
“…Even if a previous study on these wards [42] did not show that they were dominated by change resistant cultures, the present results of this present study suggest that there are indeed additional inhibiting factors that affected the outcomes of implementation of the DLDA tool [15,61] . Besides cultural characteristics, resistance to change and its impact on implementation processes [14,15,34,62] as well as time constraints and co-workers defending the old system [18,33,38,56] , the present study reveals a number of other factors that may have affected the implementation processes: time pressure; heavy workload; stress; lack of routines in using the new tool; lack of nursing staff as well as lack of time. Lack of time is also consistent with the findings of Grol and Wensing, who mean that time-consuming, complex interventions may affect the implementation process in nursing [63] .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…If the participating organizations can balance contrasting characteristics such as flexibility and firmness, then learning can be more than an individualistic and repetitive behavior (drill). New integrative strategies can be developed and implemented (collaboration exercises) (Johansson et al 2013;Alharbi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This stresses the need to support flexibility and trust, as well as stability, planning, and repetitive behavior. Alharbi et al (2014) suggest that organizations that can balance opposing characteristics seem to have the best chance to successfully implement necessary change and sustain it. This is in accordance with Quinn (1988), who asserts that effective organizations present contradictory characteristics.…”
Section: Introductionmentioning
confidence: 99%